Urban stormwater quality and load estimation from urban residential area in Skudai, Johor - R., Nazahiyah (2007)
Sampling of urban runoff was carried out in a small catchment, which represents a residential area (3.34 ha) in Skudai, Johor. One hundred and seventeen runoff samples from ten storm events were analysed. Runoff quality showed large variations in concentrations during storms, especially for SS, BOD5 and COD. Concentrations of NO3-N, NO2-N, NH3-N, and P were also high. Lead (Pb) was also detected but the levels were low (<0.001 mg/L). In general, the river quality is badly polluted and falls in Class V based on the Malaysian Interim National Water Quality Standards. Event mean concentrations for all parameters were found to vary greatly between storms. The values (mg/L) were BOD5 (72), COD (325), SS (386), NO3-N (2.5), NO2-N (0.58), NH3-N (6.8), P (3.4), respectively. First flush phenomena were observed for BOD, COD, SS, NO3-N, NH3-N and P. The first 20-30% of the runoff volume evacuated between 20-59% BOD, 15-69% COD, 15-78% SS, 14-49% NO3-N, 14-19% NO2-N, 23-53% NH3-N and 23-43% P.